Rancang Bangun Host Sistem Mini SCADA Untuk Pengontrolan Beban Trafo 20 KV Pada Gardu Induk - Ikhwanto Ikhwanto; R.A Suwodjo Kusumoputro; Novi Azman (Universitas Nasional, 2014)
In this era of globalization, the needs of remote control systems isincreasing, where the system used is more sophisticated. Similarly, when a transformeroperator in electrical substations, which will control and monitor the load transformer 20KV is still done by hand. This will result in less efficient and optimal performance of theoperator. We need a system that can control remotely. To overcome these problems, hencedesigned